Revolutionizing wearable technology: advanced fabrication techniques for body-conformable electronics - Ruilai Wei; Haotian Li; Zhongming Chen; Qilin Hua; Guozhen Shen; Kai Jiang (npj Flexible Electronics)
Abstract With the increasing demand for wearable electronic products, there is a pressing need to develop electronic devices that seamlessly conform to the contours of the human body while delivering excellent performance and reliability. Traditional rigid electronic fabrication technologies fall short of meeting these requirements, necessitating the exploration of advanced flexible fabrication technologies that offer new possibilities for designing and fabricating flexible and stretchable electronic products, particularly in wearable devices. Over time, the continuous development of innovative fabrication techniques has ushered in significant improvements in the design freedom, lightweight, seamless integration, and multifunctionality of wearable electronics. Here, we provide a comprehensive overview of the advancements facilitated by advanced fabrication technology in wearable electronics. It specifically focuses on key fabrication methods, including printed electronics fabrication, soft transfer, 3D structure fabrication, and deformation fabrication. By highlighting these advancements, it sheds light on the challenges and prospects for further development in wearable electronics fabrication technologies. The introduction of advanced fabrication technologies has revolutionized the landscape of wearable/conformable electronics, expanding their application domains, streamlining system complexity associated with customization, manufacturing, and production, and opening up new avenues for innovation and development of body-conformable electronics.